Piers′ Borane‐Induced Tetramerization of Arylacetylenes. Issue 9 (28th December 2021) - Hasenbeck, Max; Müller, Tizian; Averdunk, Arthur; Becker, Jonathan; Gellrich, Urs
Abstract: We herein report that the reaction of Piers′ borane, i. e . HB(C6 F5 )2, with an excess of arylacetylenes at room temperature leads to tetramerization of the acetylene and the diastereoselective formation of boryl‐substituted tetra‐aryl‐tetrahydropentalenes. The reaction mechanism was investigated by isotope labeling experiments and DFT computations. These investigations indicate that a series of 1, 2‐carboboration reactions form an octatetraene that undergoes an electrocyclization. Two skeletal rearrangements then presumably lead to the formation of the tetrahydropentalene core. Overall, this intricate and unprecedented transformation comprises five carbon‐carbon bond formations in a single reaction. Abstract : Electrocyclization : The formation of tetra‐aryl‐tetrahydropentalenes upon the reaction of arylacetylenes with Piers' borane (HB(C6 F5 )2 ) is reported. Isotope labeling experiments and DFT computations indicate that the mechanism of this complex transformation commences with a series of unprecedented 1, 2‐carboborations, followed by an electrocyclization and two skeletal rearrangements.